Steel foil for current collector and all-solid-state secondary battery

By using ferrite system stainless steel foil and controlling the half-height width of its X-ray diffraction curve, combined with resin coating, the problem of steel foil for current collector in all-solid secondary batteries is solved, and the problem of bending or bending at high temperature is achieved. High-efficiency cycle characteristics and capacity maintenance of the battery.

CN119156724APending Publication Date: 2024-12-17NIPPON STEEL CHEM & MATERIAL CO LTD

Patent Information

Application Number
CN202380031683.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-01-19
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In all-solid secondary batteries, steel foil for current collectors is prone to bending or bending during the heat treatment of the active material layer at high temperature, affecting the performance and life of the battery.

Method used

The ferritic stainless steel foil is used as the current collector, and the half-height width of the peak of the {110} plane in the X-ray diffraction curve with CoKα ray is 0.40-0.52°. The strain value of the foil is controlled to suppress heat shrinkage and is coated with resin. Used to improve heat resistance and flatness.

Benefits of technology

At a high temperature of around 700°C, bending or bending is difficult to occur, and the all-solid secondary battery exhibits excellent cycle characteristics and battery capacity maintenance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005066283610000231
    Figure BDA0005066283610000231
Patent Text Reader

Abstract

Provided are: a steel foil for a current collector which is less susceptible to buckling or bending when heat-treated at a high temperature at which an active material is crystallized after an active material layer is formed; and an all-solid-state secondary battery which uses the steel foil for a current collector. This steel foil for a current collector is provided with a ferritic stainless steel foil. The ferrite stainless steel foil according to the present disclosure has a full width at half maximum (Fw) of 0.40-0.52 DEG for a {110} plane peak in an X-ray diffraction curve using a CoK [alpha] ray.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a current collector steel foil for electrodes used in a battery and an all-solid-state secondary battery using the current collector steel foil. Background Technology

[0002] Until now, primary and secondary batteries have been used as power sources for various electronic devices. In recent years, with the popularization of small electronic devices such as home video cameras, laptops, and smartphones, secondary batteries, represented by lithium-ion batteries, have rapidly become more widespread.

[0003] A secondary battery includes electrodes with positive and negative electrodes, and an electrolyte. Both the positive and negative electrodes have an active material layer formed on a current collector. That is, the current collector refers to the substrate of the electrode. The active material layer refers to the layer containing the active material. The current collector has the function of supplying current to the active material and retaining the active material.

[0004] To date, metal foil has been used as the substrate for current collectors in secondary batteries. Specifically, for example, in lithium-ion batteries, copper foil is currently used as the negative electrode current collector, and aluminum foil as the positive electrode current collector. On the other hand, it is sometimes envisioned that secondary batteries will be used in harsher environments than ever before. Therefore, there is a demand for current collector substrates with higher strength and superior heat resistance than copper and aluminum foil. Consequently, stainless steel foil, which has superior strength and heat resistance compared to copper and aluminum foil, has attracted attention as a current collector substrate.

[0005] Japanese Patent Application Publication No. 2003-178753 (Patent Document 1) and Japanese Patent Application Publication No. 2016-186881 (Patent Document 2) disclose the technology of applying stainless steel foil to current collectors.

[0006] Patent Document 1 discloses a lithium battery in which the current collector of the positive electrode is composed of a ferritic stainless steel foil with a thickness of less than 12 μm. Patent Document 1 discloses that the use of ferritic stainless steel foil as the current collector is because, compared with austenitic stainless steels such as SUS304 and SUS316, ferritic stainless steel has good machinability and is suitable for making thin foils, thereby improving productivity.

[0007] Patent Document 2 discloses a lithium-ion battery negative electrode in which the current collector is a stainless steel foil or a nickel-plated steel plate with a thickness of less than 15 μm. Patent Document 2 discloses that stainless steel foil and nickel-plated steel plate are used as current collectors because of their high strength and the fact that their strength does not decrease even after heat treatment at around 300°C, and that they can maintain their initial strength even after imidization and imidization treatments at high temperatures.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Application Publication No. 2003-178753

[0011] Patent Document 2: Japanese Patent Application Publication No. 2016-186881 Summary of the Invention

[0012] The problem the invention aims to solve

[0013] As proposed in Patent Documents 1 and 2 above, high-strength current collectors can be obtained with high productivity by using stainless steel foil as the substrate for the current collector. However, in recent years, in order to balance high energy density and safety, the development of all-solid-state secondary batteries is being accelerated. All-solid-state secondary batteries refer to secondary batteries that use solid electrolytes instead of the electrolytes used in previous secondary batteries, and whose electrodes, electrolytes, including the current collector and active material layer, are all made of solids.

[0014] In the case of all-solid-state secondary batteries, after an active material layer is formed on the surface of the current collector, the active material is sometimes crystallized to obtain good battery characteristics. In this case, for example, the current collector with the active material layer formed on its surface is heat-treated at a high temperature of around 700°C. However, if the active material crystallizes due to this high-temperature heat treatment, the active material layer will shrink. As a result, the current collector may buckle or bend due to dimensional changes caused by the thermal shrinkage of the active material layer and the current collector.

[0015] That is, assuming that the current collector steel foil is used in an all-solid-state secondary battery, it is preferable that even if the active material layer shrinks due to heat treatment at a high temperature of, for example, around 700°C, the current collector steel foil is unlikely to be bent or kinked. However, the aforementioned patent documents 1 and 2 do not investigate the possibility of bending or kinking when the active material is crystallized, as in all-solid-state secondary batteries.

[0016] The purpose of this disclosure is to provide a current collector steel foil and an all-solid-state secondary battery using the current collector steel foil, wherein the current collector steel foil is difficult to bend or bend when heat-treated at a high temperature to achieve the degree of crystallization of the active material after forming an active material layer.

[0017] Solution for solving the problem

[0018] The current collector steel foil disclosed herein includes ferritic stainless steel foil.

[0019] The full width at half maximum (Fw) of the peak on the {110} plane of the ferritic stainless steel foil in the X-ray diffraction curve using CoKα rays is 0.40–0.52°.

[0020] The all-solid-state secondary battery disclosed herein has the following characteristics:

[0021] The aforementioned current collector uses steel foil;

[0022] Active material layer;

[0023] Solid electrolyte layer; and

[0024] Current collector layer.

[0025] The effects of the invention

[0026] The steel foil for current collectors disclosed herein is difficult to bend or twist when heat-treated at a high temperature to achieve the desired degree of crystallization after the formation of the active material layer. Detailed Implementation

[0027] First, the inventors considered using ferritic stainless steel foil as the substrate for the current collector foil. Compared to non-ferrous metal foils such as aluminum foil, ferritic stainless steel foil exhibits higher stability at high temperatures. Furthermore, compared to austenitic stainless steel foil, ferritic stainless steel foil has lower resistance and higher conductivity. Based on these considerations, the inventors decided to use ferritic stainless steel foil as the substrate for the current collector foil.

[0028] As described above, assuming the current collector steel foil is used in an all-solid-state secondary battery, it is preferable that even if the active material layer shrinks due to heat treatment at a high temperature of around 700°C, the current collector steel foil is unlikely to bend or deform. Therefore, the inventors conducted a detailed study on steel foil that is unlikely to bend or deform when heat-treated at a high temperature of around 700°C. Based on the results of this detailed study, the inventors believe that if the current collector steel foil also shrinks to some extent when the active material layer shrinks due to thermal shrinkage as the active material crystallizes, then bending or deforming of the current collector steel foil can be suppressed.

[0029] Specifically, the inventors focused on the strain of ferritic stainless steel foil, which serves as the substrate for current collector steel foil. If the strain of the ferritic stainless steel foil can be controlled, it is possible to control the thermal shrinkage of the current collector steel foil during heat treatment at approximately 700°C after the formation of the active material layer. As a result, when heat-treated at approximately 700°C, it is possible to suppress the occurrence of buckling or bending of the current collector steel foil with the active material layer formed thereon.

[0030] Based on the above understanding, the inventors conducted a detailed study and found that if the full width at half maximum (Fw) of the peak of the {110} plane in the X-ray diffraction curve of the ferritic stainless steel foil using CoKα rays is 0.40 to 0.52°, then when the current collector steel foil with the active material layer formed is heat-treated at around 700°C, the occurrence of bending or crimping can be suppressed.

[0031] If the full width at half maximum (Fw) of the {110} plane peak in the X-ray diffraction curve using CoKα rays for ferritic stainless steel foil is too small, the strain of the ferritic stainless steel foil is too low. In this case, no strain is released during heat treatment at around 700°C, and no thermal shrinkage occurs during heat treatment. As a result, the current collector foil bends due to the thermal shrinkage of the active material layer. On the other hand, if the Fw of the {110} plane of the ferritic stainless steel foil is too large, the strain of the ferritic stainless steel foil is too high. In this case, excessive strain is released during heat treatment at around 700°C, and excessive thermal shrinkage occurs during heat treatment. As a result, the thermal shrinkage exceeds the thermal shrinkage of the active material layer, causing the current collector foil to buckle.

[0032] Therefore, the half-width at half-maximum (Fw) of the peak of the {110} plane of the ferritic stainless steel foil of the current collector according to this embodiment is set to 0.40 to 0.52°. As a result, after an active material layer is formed on the surface of the current collector steel foil according to this embodiment, it is difficult to bend or flex even after heat treatment at around 700°C.

[0033] The key points of the current collector steel foil involved in this embodiment, which is based on the above understanding, are as follows. [1]

[0035] A current collector steel foil comprising a ferritic stainless steel foil.

[0036] The full width at half maximum (Fw) of the peak on the {110} plane of the ferritic stainless steel foil in the X-ray diffraction curve using CoKα rays is 0.40–0.52°. [2]

[0038] According to the current collector steel foil described in [1], wherein,

[0039] On the surface of the ferritic stainless steel foil.

[0040] When the arithmetic mean roughness in any direction is defined as Ra1 and the arithmetic mean roughness in the direction perpendicular to the arbitrary direction is defined as Ra2, both Ra1 and Ra2 are 0.03 to 0.30 μm. [3]

[0042] According to the current collector steel foil described in [1], wherein,

[0043] The thickness of the ferritic stainless steel foil is 5–60 μm. [4]

[0045] According to the current collector steel foil described in [2], wherein,

[0046] The thickness of the ferritic stainless steel foil is 5–60 μm. [5]

[0048] According to the current collector steel foil described in [1], wherein,

[0049] A resin coating is formed on the surface of the ferritic stainless steel foil. [6]

[0051] According to the current collector steel foil described in [2], wherein,

[0052] A resin coating is formed on the surface of the ferritic stainless steel foil. [7]

[0054] According to the current collector steel foil described in [3], wherein,

[0055] A resin coating is formed on the surface of the ferritic stainless steel foil. [8]

[0057] According to the current collector steel foil described in [4], wherein,

[0058] A resin coating is formed on the surface of the ferritic stainless steel foil. [9]

[0060] A type of all-solid-state secondary battery, which has the following characteristics:

[0061] Steel foil for current collectors as described in any one of [1] to [8];

[0062] Active material layer;

[0063] Solid electrolyte layer; and

[0064] Current collector layer.

[0065] The current collector steel foil according to this embodiment will be described below.

[0066] [Steel foil for current collectors]

[0067] The current collector steel foil according to this embodiment includes a ferritic stainless steel foil as the base material. Alternatively, the current collector steel foil according to this embodiment may also include structures other than ferritic stainless steel foil.

[0068] Ferritic stainless steel foil

[0069] The substrate of the current collector steel foil involved in this embodiment is ferritic stainless steel foil. Specifically, ferritic stainless steel foil refers to steel foil with a Cr content of 10.5% or more and a microstructure mainly composed of ferrite. In this specification, a microstructure mainly composed of ferrite means that the volume fraction of ferrite in the microstructure is 95% or more.

[0070] In this embodiment, the ferritic stainless steel foil can be a metal foil made of a known ferritic stainless steel. For example, the ferritic stainless steel foil involved in this embodiment can be SUS405 as specified in JIS G 4305 (2012), SUS410L, SUS429, SUS430, SUS430LX, SUS430J1L, SUS434, SUS436L, SUS436J1L, SUS443J1, SUS444, SUS445J1, SUS445J2, SUS447J1, or SUSSXM27.

[0071] The ferritic stainless steel foil involved in this embodiment can also be, for example, 403 as specified in ASTM A280 (2006), 405, 409L, 410, 410L, 410S, 415, 420J1, 420J2, 420, 429, 429J1, 430, 430J1L, 430LX, 430Ti, 434, 436, 436J1L, 439, 441, 444, 445, 445J1, 445J2, 446, 447, or 448.

[0072] The thickness of the ferritic stainless steel foil involved in this embodiment is preferably 5 to 60 μm. The thinner the ferritic stainless steel foil, the thinner the current collector foil. As a result, the energy density of the battery using the electrode manufactured with this current collector foil can be increased. However, if the ferritic stainless steel foil is too thin, it is difficult to manufacture the current collector foil. Therefore, in this embodiment, the thickness of the ferritic stainless steel foil is preferably 5 to 60 μm.

[0073] [Fw, the full width at half maximum (Fw) of the peak on the {110} plane]

[0074] The ferritic stainless steel foil of this embodiment exhibits a full width at half maximum (Fw) of 0.40–0.52° for the peak on the {110} plane in an X-ray diffraction curve using CoKα rays. As a result, the current collector steel foil based on the ferritic stainless steel foil of this embodiment is difficult to bend or flex when heat-treated at around 700°C after the formation of the active material layer.

[0075] If the half-width at half-maximum (Fw) of the {110} face of the ferritic stainless steel foil is too small, the strain of the ferritic stainless steel foil is too low. In this case, when heat-treated at around 700°C, the strain will not be released, and no thermal shrinkage will occur during heat treatment. As a result, the current collector foil will bend due to the thermal shrinkage of the active material layer. On the other hand, if the half-width at half-maximum (Fw) of the {110} face of the ferritic stainless steel foil is too large, the strain of the ferritic stainless steel foil is too high. In this case, when heat-treated at around 700°C, the strain will be excessively released, and excessive thermal shrinkage will occur during heat treatment. As a result, the thermal shrinkage exceeds the thermal shrinkage of the active material layer, causing the current collector foil to buckle.

[0076] The preferred lower limit of the half-width at half-maximum (Fw) of the {110} facet of the ferritic stainless steel foil according to this embodiment is 0.41, more preferably 0.43, and even more preferably 0.45. If the Fw of the {110} facet is 0.45 or higher, bending during heat treatment at around 700°C after the formation of the active material layer can be further suppressed. The preferred upper limit of the Fw of the {110} facet of the ferritic stainless steel foil according to this embodiment is 0.51, more preferably 0.50, and even more preferably 0.48.

[0077] In this embodiment, the full width at half maximum (Fw) of the {110} plane of a ferritic stainless steel foil can be determined by the following method. A test piece is prepared from the current collector steel foil described in this embodiment. The size of the test piece is not particularly limited, and the thickness of the test piece is the same as the thickness of the steel foil. The observation surface of the test piece is measured using grazing incident X-ray diffraction (GIXD). Specifically, the X-ray source is CoKα rays, the tube voltage is 40 kV, and the tube current is 135 mA. The X-ray beam is paralleled by a mirror. The incident angle of the Solvay slit is 5°, and the diffraction angle is 2.5°. Twelve conditions are set within the range of 1 to 25° of the incident angle, resulting in twelve measurement points within the range of 0.19 to 4.60 μm from the observation surface of the test piece. At each measurement point, the peak of the {110} plane is determined, and the full width at half maximum (Fw) is calculated. The arithmetic mean of the 12 obtained half-widths (FWs) is defined as the FW of the {110} plane. The depth of measurement is determined by calculating the X-ray penetration depth t with the linear absorption coefficient set to μ and satisfying μt = 1, and converting it to the depth from the observation surface of the test piece. Furthermore, the mass absorption coefficient is 19.11Cr-1.77Mo-78.38Fe (mass%). Additionally, the density of the ferritic stainless steel foil is 7.75 g / cm³. 3 .

[0078] [Arithmetic mean roughness Ra1 and Ra2]

[0079] Preferably, on the surface of the ferritic stainless steel foil involved in this embodiment, when the arithmetic mean roughness in any direction is defined as Ra1 and the arithmetic mean roughness in the direction perpendicular to Ra1 is defined as Ra2, both Ra1 and Ra2 are 0.03 to 0.30 μm.

[0080] Here, an all-solid-state secondary battery is used by repeatedly charging and discharging it. On the other hand, in secondary batteries, the charge and discharge capacity tends to decrease with repeated charging and discharging. Therefore, for an all-solid-state secondary battery, it is preferable to maintain the charge and discharge capacity even with repeated charging and discharging. In this specification, "maintaining the charge and discharge capacity even with repeated charging and discharging" is also referred to as "having excellent cycle characteristics".

[0081] That is, all-solid-state secondary batteries preferably possess excellent cycle characteristics. Therefore, the inventors conducted a detailed study on the current collector steel foil used to obtain all-solid-state secondary batteries with excellent cycle characteristics. Specifically, the inventors manufactured ferritic stainless steel foils with a full width at half maximum (Fw) of 0.40–0.52° for various {110} peaks and produced simulated all-solid-state secondary batteries. The simulated batteries were repeatedly charged and discharged multiple times to evaluate the battery's capacity retention rate (capacity retention). As a result, the inventors made a novel discovery: the surface roughness of the ferritic stainless steel foil affects the cycle characteristics of the all-solid-state secondary battery.

[0082] First, considering that the surface roughness of ferritic stainless steel foil sometimes exhibits anisotropy, the inventors focused on the arithmetic mean roughness in two directions of the surface. Specifically, in this specification, the arithmetic mean roughness in any direction of the surface of the ferritic stainless steel foil is defined as Ra1, and the arithmetic mean roughness in the direction perpendicular to Ra1 is defined as Ra2. For example, when Ra1 is the arithmetic mean roughness in the rolling direction of the ferritic stainless steel foil, Ra2 is the arithmetic mean roughness in the width direction of the ferritic stainless steel foil.

[0083] The inventors conducted detailed research and found that when Ra1 or Ra2 is less than 0.03 μm, the battery capacity retention rate sometimes gradually decreases due to repeated charge-discharge cycles. Furthermore, when Ra1 or Ra2 is greater than 0.30 μm, the capacity retention rate sometimes drops rapidly during repeated charge-discharge cycles. Specifically, the inventors conducted detailed research and found that when using ferritic stainless steel foil with a full width at half maximum (Fw) of 0.40–0.52° for the {110} peak as the substrate for the current collector foil in an all-solid-state secondary battery, if both Ra1 and Ra2 satisfy 0.03–0.30 μm, an all-solid-state secondary battery that is not only resistant to bending or twisting but also exhibits excellent cycle characteristics can be obtained. The inventors speculate on the reasons for this as follows.

[0084] First, when manufacturing all-solid-state secondary batteries using current collector steel foil based on ferritic stainless steel foil, a thin film, typically an active material layer, is laminated and formed on the surface of the steel foil. Alternatively, vacuum deposition methods, such as sputtering or electron beam evaporation, are sometimes used to form the thin film. In all-solid-state secondary batteries, by using vacuum deposition methods, the thin film laminated on the surface of the steel foil is formed very thinly and uniformly. As a result, in all-solid-state secondary batteries, the surface roughness of the ferritic stainless steel foil as the substrate and the surface roughness of the thin film, such as the active material layer, can easily reach the same level.

[0085] Furthermore, in all-solid-state secondary batteries, redox reactions occur in metals during charging and discharging, during which some metals may react. In this case, the reacting metal grows into dendrites, potentially leading to a short circuit. Additionally, if the surface roughness of the ferritic stainless steel foil is too high, the surface roughness of the films (active material layer, electrolyte layer, etc.) stacked on the foil surface will also increase. In this case, the shapes of the interfaces between the current collector foil and the films, and between the films themselves, become complex, tending to induce metal reactions and dendrite growth. That is, the greater the surface roughness of the ferritic stainless steel foil used as the current collector substrate, the more likely a short circuit may occur during charging and discharging. Therefore, the inventors hypothesize that the capacity retention rate will decrease sharply during repeated charging and discharging.

[0086] On the other hand, if the surface roughness of the ferritic stainless steel foil is too small, the surface roughness of the film laminated on the surface of the foil will also be small. In this case, the interface between the current collector foil and the film, and the interfaces between the films themselves, will become too smooth. As a result, the adhesion of the film decreases, and the film may easily peel off due to the volume expansion and contraction of the active material layers during charging and discharging. Therefore, the inventors speculate that the charge and discharge capacity of the battery will gradually decrease due to repeated charging and discharging.

[0087] Based on the above mechanism, the inventors hypothesize that when a ferritic stainless steel foil with a full width at half maximum (Fw) of 0.40–0.52° for the {110} plane peak is used as the substrate for the current collector steel foil in an all-solid-state secondary battery, after forming an active material layer on the surface by ensuring that both Ra1 and Ra2 are 0.03–0.30 μm, it is difficult to bend or flex even after heat treatment at around 700°C. Furthermore, an all-solid-state secondary battery with excellent cycle characteristics can be obtained. Alternatively, based on a mechanism different from the above, after forming an active material layer on the surface of the current collector steel foil satisfying the structure of this embodiment, it is difficult to bend or flex even after heat treatment at around 700°C. Furthermore, an all-solid-state secondary battery using this current collector steel foil may also obtain excellent cycle characteristics. However, the following embodiments demonstrate that when ferritic stainless steel foil with a full width at half maximum (Fw) of 0.40 to 0.52° of the {110} plane peak is used as the substrate for the current collector foil of the all-solid-state secondary battery, after forming an active material layer on the surface by ensuring that Ra1 and Ra2 both satisfy 0.03 to 0.30 μm, even if heat treatment at around 700°C is performed, it is difficult to produce bending or flexing, and an all-solid-state secondary battery with excellent cycle characteristics can be obtained.

[0088] Furthermore, when Ra1 or Ra2 is greater than 0.30 μm, the mechanism that easily leads to short circuits during the charging and discharging of all-solid-state secondary batteries, as described above, makes short circuits more likely to occur at locations where the unevenness of the steel foil surface is locally increased. Therefore, the maximum roughness Rz among the surface roughness parameters may play a dominant role in influencing whether short circuits are easily caused by this mechanism. However, it has been confirmed that the arithmetic mean roughness Ra and the maximum roughness Rz of the ferritic stainless steel foil involved in this embodiment have the same tendency. Therefore, in this embodiment, the arithmetic mean roughness Ra1 and Ra2 in two perpendicular directions are used as indicators of sealing and short-circuit resistance.

[0089] The preferred lower limit for Ra1 and Ra2 of the surface of the ferritic stainless steel foil according to this embodiment is 0.04 μm, and more preferably 0.05 μm. The preferred upper limit for Ra1 and Ra2 of the surface of the ferritic stainless steel foil according to this embodiment is 0.29 μm, and more preferably 0.28 μm.

[0090] In this embodiment, the surface roughness Ra1 and Ra2 of a ferritic stainless steel foil can be measured using the following method. First, a test piece is cut from the ferritic stainless steel foil according to this embodiment and fixed to a glass substrate. Three arbitrary locations are determined from the surface of the fixed test piece and used as measurement locations. At each measurement location, an arbitrary direction is designated as "Direction 1," and a direction perpendicular to Direction 1 is designated as "Direction 2." Direction 1 is preferably a direction parallel to the rolling direction of the ferritic stainless steel foil. However, even those skilled in the art may not be able to determine the rolling direction of the ferritic stainless steel foil. In this case, the direction for measuring the arithmetic mean roughness may not be parallel to the rolling direction.

[0091] At each measurement location, the arithmetic mean roughness in direction 1 and direction 2 is measured according to the method specified in JIS B 0601 (2001), and defined as Ra1 (μm) and Ra2 (μm). The roughness meter used for measuring the arithmetic mean roughness can be, for example, the Surftest SJ-301 (trade name) surface roughness measuring machine manufactured by Mitutoyo Co., Ltd., which is a contact roughness meter. Specifically, the conditions for calculating the roughness curve are as follows.

[0092] Measuring force: 0.75mN

[0093] Stylus tip shape (when using a contact roughness meter): 2μm R60°

[0094] Cutoff value λc: 0.25mm

[0095] Cutoff value λs: 2.5μm

[0096] Number of intervals: 5

[0097] Measurement speed: 0.25 mm / s

[0098] Reference length: 0.25mm

[0099] Evaluation length: 1.25mm

[0100] [Resin Coating]

[0101] The current collector steel foil according to this embodiment can have a resin coating formed on the surface of a ferritic stainless steel foil. By forming a resin coating on the surface of the ferritic stainless steel foil, the insulation, heat resistance, and flatness of the current collector steel foil can be improved. Furthermore, in this embodiment, the resin coating can be formed on both sides of the ferritic stainless steel foil, on only one side, or not at all. The resin coating can also be formed on a portion of one side of the ferritic stainless steel foil, or on the entire single side of the ferritic stainless steel foil.

[0102] The resin coating is not particularly limited; for example, it can be an inorganic-organic mixed resin coating. An inorganic-organic mixed resin coating refers to a resin coating formed by combining inorganic and organic components. Specifically, the inorganic-organic mixed resin coating can also be a siloxane coating having an inorganic backbone with a three-dimensional network structure of siloxane bonds as the main framework, wherein at least one crosslinked oxygen in the backbone is replaced by an organic group and / or a hydrogen atom. That is, in this embodiment, as the resin coating, a siloxane coating in which the oxygen concentration [O] (mol / L) and silicon concentration [Si] (mol / L) satisfy 1 < [O] / [Si] < 2 can be used.

[0103] As described above, the thinner the current collector steel foil, the higher the energy density of the battery using electrodes manufactured with that current collector steel foil. Therefore, in this embodiment, when forming the resin coating, a thinner resin coating thickness is preferable. On the other hand, if the resin coating thickness is too thin, the aforementioned insulation, heat resistance, and flatness may not be sufficiently obtained. Therefore, in this embodiment, when forming the resin coating, the resin coating thickness is preferably 0.3 to 5.0 μm.

[0104] [Other Structures]

[0105] The current collector steel foil described in this embodiment may include ferritic stainless steel foil, resin coating, and other structures. For example, a layer other than the resin coating may be formed on the surface of the current collector steel foil. In this case, the layer other than the resin coating preferably has electrical conductivity.

[0106] [Battery]

[0107] As described above, by forming an active material layer on or above the current collector steel foil according to this embodiment, it can be used as an electrode of a battery. Here, the current collector steel foil according to this embodiment can be used as a positive electrode current collector steel foil or a negative electrode current collector steel foil. Furthermore, the type of battery to which the current collector steel foil according to this embodiment is applied is not limited. The current collector steel foil according to this embodiment can be used as an electrode of an all-solid-state secondary battery, as an electrode of a non-aqueous electrolyte secondary battery, as an electrode of an aqueous electrolyte secondary battery, or as an electrode of a primary battery.

[0108] [All-solid-state rechargeable battery]

[0109] The battery involved in this embodiment is preferably an all-solid-state secondary battery. When the battery involved in this embodiment is an all-solid-state secondary battery, the all-solid-state secondary battery includes the current collector steel foil, active material layer, solid electrolyte layer and current collector layer involved in this embodiment.

[0110] The all-solid-state secondary battery according to this embodiment includes an active material layer. Here, the active material layer is not particularly limited and can be obtained by a thin film containing a known active material. When the active material layer is a positive electrode active material layer, the positive electrode active material can be, for example, lithium cobalt oxide, a ternary material, lithium manganese oxide, lithium iron phosphate, or a high-nickel material. When the active material layer is a negative electrode active material layer, the negative electrode active material can be, for example, a carbon-based material represented by graphite, an alloy material represented by CuSn alloy or NiTiSi alloy, or a Si-based material represented by SiO. Alternatively, in an all-solid-state secondary battery, a negative electrode active material layer may not be formed. In this case, the active material layer refers to the positive electrode active material layer.

[0111] More specifically, when the current collector steel foil described in this embodiment is used in an all-solid-state lithium-ion secondary battery, the positive electrode active material can be, for example, molybdenum oxide (MoO3), vanadium oxide (V2O3), lithium manganese oxide (LiMn2O4), lithium cobalt oxide (LiCoO2), solid solution oxide (Li2MnO3-LiMO2 (M = Co, Ni, etc.)), lithium-manganese-nickel oxide (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 Composite oxides such as O2, olivine-type lithium phosphorus oxide (LiFePO4), and tungsten oxide (WO3).

[0112] Furthermore, in this embodiment, the method for forming the active material layer using the active material described in the above example is not particularly limited. For example, vacuum deposition methods such as sputtering and electron beam evaporation can be used to form the active material layer. Moreover, as mentioned above, for all-solid-state secondary batteries, after forming the active material layer on the surface of the current collector, the active material is sometimes crystallized. In this case, after forming the active material layer on or above the current collector steel foil, heat treatment is performed at a high temperature of, for example, around 700°C. The current collector steel foil according to this embodiment is difficult to bend or flex even after heat treatment at around 700°C following the formation of the active material layer.

[0113] The all-solid-state secondary battery according to this embodiment also includes a solid electrolyte layer. The solid electrolyte layer is not particularly limited and can be obtained by using a thin film containing a known solid electrolyte. Specifically, when the all-solid-state secondary battery according to this embodiment is a thin-film all-solid-state lithium-ion secondary battery, Li7Al can be used as the solid electrolyte, for example. 0.1 La3Zr2O 12 Li 1.3 Al 0.3 Ti 1.7 (PO4)3, (Li, La)TiO3, Li5La3Ti2O 12 Li 3.09 BO 2.53 N 0.52 ,Li3PON4.

[0114] The all-solid-state secondary battery according to this embodiment also includes a current collector layer. As described above, the current collector steel foil according to this embodiment can be used as a positive electrode current collector steel foil or as a negative electrode current collector steel foil. When the current collector steel foil according to this embodiment is used as a positive electrode current collector steel foil, the current collector layer is used as a negative electrode current collector. When the current collector steel foil according to this embodiment is used as a negative electrode current collector steel foil, the current collector layer is used as a positive electrode current collector.

[0115] In this embodiment, the material used for the current collector layer can be a known material selected from the perspective of electrochemical corrosion resistance and volume resistivity at the operating potential of the positive and negative electrodes. When the current collector layer is used as a positive electrode current collector, it can be, for example, platinum (Pt), gold (Au), aluminum (Al), or titanium nitride (TiN). When the current collector layer is used as a negative electrode current collector, it can be, for example, platinum (Pt), gold (Au), silver (Ag), copper (Cu), nickel (Ni), or titanium nitride (TiN).

[0116] The all-solid-state secondary battery according to this embodiment may include the current collector steel foil, active material layer, solid electrolyte layer, current collector layer, and other structures as described in this embodiment. For example, a conductive layer may be formed between the current collector steel foil and the active material layer according to this embodiment. That is, in the all-solid-state secondary battery according to this embodiment, the conductive layer has any structure. When a conductive layer is formed between the current collector steel foil and the active material layer, diffusion between the current collector steel foil and the active material layer can be suppressed. At this time, the interfacial resistance between the current collector steel foil and the active material layer can also be suppressed.

[0117] In the all-solid-state secondary battery according to this embodiment, when forming the conductive layer, the material used for the conductive layer can be a known material selected from the perspective of electrochemical corrosion resistance and volume resistivity value at the operating potential of the positive and negative electrodes. For example, platinum (Pt), gold (Au), aluminum (Al), and titanium nitride (TiN) can be used as the conductive layer on the positive electrode side. For example, platinum (Pt), gold (Au), silver (Ag), copper (Cu), nickel (Ni), and titanium nitride (TiN) can be used as the conductive layer on the negative electrode side.

[0118] The all-solid-state secondary battery according to this embodiment may also include the current collector steel foil, conductive layer, active material layer, solid electrolyte layer, current collector layer, and other structures as described in this embodiment. In this case, for example, a protective layer protecting the active material layer may be included, or a casing covering the entire battery may be included. Furthermore, when a protective layer and casing are present, it is preferable that the protective layer and casing are not conductive.

[0119] [Pressed]

[0120] The current collector steel foil according to this embodiment is difficult to bend or flex during heat treatment at a high temperature to achieve the desired degree of crystallization after the formation of the active material layer. In this embodiment, the difficulty in bend formation can be evaluated using the following method.

[0121] Lithium cobalt oxide (LiCoO2) is used as the active material, and an active material layer is formed on the surface of the current collector steel foil according to this embodiment. The dimensions of the current collector steel foil are, for example, 300 to 600 mm in the width direction. Tension is applied to the current collector steel foil, on which the active material has been formed by vacuum film deposition, using a conveyor roller with a diameter of 70 mm or more, while simultaneously subjecting it to a heat treatment at 700°C for 20 minutes. The applied tension is, for example, 5 to 50 N / mm in the rolling direction of the steel foil. 2Additionally, the conveying speed during heat treatment is 0.1 to 30.0 m / min. Visually inspect the heat-treated current collector steel foil for any warping. In this specification, warping refers to the unevenness formed on the surface of the current collector steel foil. Based on the visual inspection, if no warping is observed on the current collector steel foil, it is determined that warping is unlikely to occur.

[0122] [bending]

[0123] The current collector steel foil according to this embodiment is difficult to bend or twist when subjected to heat treatment at a high temperature to achieve the desired degree of crystallization after the formation of the active material layer. In this embodiment, the difficulty in bending can be evaluated using the following method.

[0124] A test piece is made from the current collector steel foil according to this embodiment. The dimensions of the test piece are 30 mm in the rolling direction of the ferritic stainless steel foil and 150 mm in the width direction. Lithium cobalt oxide (LiCoO2) is used as the active material to form an active material layer on the surface of the test piece, and it is heat-treated at 700°C for 20 minutes. One end of the heat-treated test piece in the longitudinal direction is fixed to the upper end of a right-angle platform, and the test piece is positioned in contact with the right-angle platform. The distance between the other end (lower end) of the test piece in the longitudinal direction and the right-angle platform is measured with a ruler and defined as the "warpage amount" of the test piece. In this embodiment, when the warpage amount is 5 mm or less, it is determined that bending is difficult. Furthermore, in this embodiment, when the warpage amount is 3 mm or less, it is determined that bending is very difficult.

[0125] [Cyclic Characteristics]

[0126] The current collector steel foil involved in this embodiment can preferably yield an all-solid-state secondary battery with excellent cycle characteristics. In this embodiment, the excellent cycle characteristics of the all-solid-state secondary battery can be evaluated by the following method.

[0127] First, a simulated product simulating an all-solid-state secondary battery is fabricated. Specifically, a test piece is cut from the current collector steel foil according to this embodiment. A positive electrode conductor layer is formed on the cut test piece by sputtering. For example, a DC (Direct Current) sputtering apparatus is used, with Pt as the target material, and sputtering is performed in an Ar atmosphere without heating to achieve a film thickness of 1.0 μm.

[0128] A positive electrode active material layer is formed on the formed positive electrode conductive layer by sputtering. For example, a device using RF (Radio Frequency) sputtering is used to sputter lithium cobalt oxide (LiCoO2) to a film thickness of 0.45 μm.

[0129] The test piece with the positive electrode active material layer formed is subjected to annealing. Annealing is performed at a temperature of 600°C. A solid electrolyte layer is formed on the positive electrode active material layer of the annealed test piece by sputtering. For example, sputtering is performed using an RF sputtering apparatus to achieve a lithium nitride phosphate (Li3PON4) film thickness of 1.4 μm.

[0130] A negative electrode current collector layer is formed on the solid electrolyte layer by sputtering. For example, a DC sputtering apparatus is used to sputter a copper (Cu) film with a thickness of 1.0 μm. A protective layer is then formed on the formed negative electrode current collector layer by sputtering. For example, an RF sputtering apparatus is used to sputter a silicon dioxide (SiO2) film with a thickness of 0.05 to 1.0 μm. In this embodiment, a simulated all-solid-state secondary battery is fabricated as described above.

[0131] Cycling characteristics were evaluated using a simulated product. Specifically, the simulated product was charged at a constant current of 0.1C at a rate of C until it reached 4.2V from its resting potential. Then, it was charged at a constant voltage of 4.2V for 20 hours. The simulated product charged using the above method was then discharged at a constant current of 0.1C at a rate of C until it reached 3.0V. The discharge capacity of this constant current discharge is defined as the initial discharge capacity Qd1 (mAh).

[0132] Here, a cycle consists of constant current charging at 0.1C until 4.2V is reached, constant voltage charging at 4.2V for 20 hours, and constant current discharging at 0.1C until 3.0V is reached. Nine charge-discharge cycles were further performed on the simulated product whose initial discharge capacity Qd1 (mAh) was measured. When the initial discharge capacity Qd1 (mAh) is set as the first cycle, the discharge capacity of the constant current discharge in the tenth cycle is defined as the discharge capacity Qd10 (mAh) of the tenth cycle. In this embodiment, the capacity retention rate is defined by the following formula (1).

[0133] Capacity retention rate (%) = 100 × Qd10 / Qd1 (1)

[0134] [Manufacturing method of steel foil for current collectors]

[0135] An example of a method for manufacturing the current collector steel foil according to this embodiment will be described. The manufacturing method described below is an example for manufacturing the current collector steel foil according to this embodiment; however, the manufacturing method for the current collector steel foil according to this embodiment may also be a method other than the one described below. However, the manufacturing method described below is a preferred example of the manufacturing method for the current collector steel foil according to this embodiment. The manufacturing method for the current collector steel foil according to this embodiment includes an intermediate steel preparation step, a final cold rolling step, and a heat treatment step.

[0136] [Intermediate Steel Preparation Process]

[0137] In the intermediate steel preparation process, intermediate steel with the same chemical composition as the ferritic stainless steel foil used as the substrate for the current collector is prepared. That is, the intermediate steel refers to the intermediate product used in manufacturing the ferritic stainless steel foil according to this embodiment, and is a steel plate with a thickness of tens to hundreds of μm. For example, the intermediate steel is a cold-rolled coil obtained by cold rolling hot-rolled coil. The intermediate steel can be prepared through manufacturing or by purchasing from a third party. In other words, the process for preparing the intermediate steel is not particularly limited.

[0138] When manufacturing intermediate steel, for example, it can be produced by: producing molten steel with the desired chemical composition; using the molten steel to produce billets (slabs, large billets, or small billets) via continuous casting; or using the molten steel to produce steel ingots (cast ingots). If necessary, slabs, large billets, or ingots can be pre-rolled to produce small billets.

[0139] The manufactured billets or ingots (slabs, large billets, small billets, or castings) are hot-worked and cold-rolled to produce steel plates with a thickness of tens to hundreds of μm. The hot-working method is not particularly limited; any known method may be used. Hot-working, for example, is hot rolling. When manufacturing intermediate steel by hot rolling, for example, it can be produced by the following method.

[0140] After heating the manufactured billet or ingot, rough rolling and finish rolling are performed. The hot rolling conditions are not particularly limited; appropriately known conditions can be set. If necessary, the hot-rolled intermediate steel can be repeatedly subjected to cold rolling and annealing. If necessary, the hot-rolled intermediate steel can also be surface-finished. The hot-rolled and / or cold-rolled intermediate steel is further annealed. Through the above processes, the intermediate steel according to this embodiment is prepared.

[0141] [Final cold rolling process]

[0142] In the final cold rolling process, the intermediate steel prepared in the intermediate steel preparation process is cold rolled. In this embodiment, known equipment can be used to perform the cold rolling, and there is no particular limitation. For example, a continuous rolling mill equipped with multiple cold rolling mills can be used.

[0143] In the final cold rolling process of this embodiment, the surface roughness of the roll surface, expressed as an arithmetic mean roughness Ra, is preferably 0.03 to 0.30 μm. If the surface roughness of the roll surface is too small, the surface roughness of the manufactured ferritic stainless steel foil may be too small. On the other hand, if the surface roughness of the roll surface is too large, the surface roughness of the manufactured ferritic stainless steel foil may be too large. Therefore, in the final cold rolling process of this embodiment, the arithmetic mean roughness Ra of the roll surface is preferably 0.03 to 0.30 μm.

[0144] In the final cold rolling process of this embodiment, a reduction rate R of 35% to 98% is further preferred. Here, the reduction rate R in the final cold rolling process refers to the reduction rate (%) of the thickness of the intermediate steel from before to after the final cold rolling process. That is, the reduction rate R in the final cold rolling process is defined by the following formula (A).

[0145] R(%) = [{(thickness of intermediate steel before final cold rolling) - (thickness of intermediate steel after final cold rolling)}] / (thickness of intermediate steel before final cold rolling) × 100 (A)

[0146] If the reduction R in the final cold rolling process is too low, the energy of the strain introduced into the intermediate steel through cold rolling decreases. In this case, the heat treatment temperature required to release the strain in the subsequent heat treatment process becomes higher. That is, if the reduction R in the final cold rolling process is too low and the heat treatment temperature in the subsequent heat treatment process is too low, the half-width Fw of the {110} plane in the ferritic stainless steel foil for current collectors may become too high. As a result, the current collector foil is prone to buckling when heat-treated at the high temperature required to crystallize the active material.

[0147] Furthermore, during the final cold rolling process, as the foil strip is rolled down, its surface is transferred to follow the surface shape of the rolls, thus altering the surface roughness of the intermediate steel. Therefore, if the reduction rate in the final cold rolling process is too low, the surface roughness of the foil strip cannot be controlled, and the roughness formed on the surface of the intermediate steel will remain, potentially resulting in excessive surface roughness. In this case, the Ra1 and / or Ra2 of the manufactured ferritic stainless steel foil surface may exceed 0.30 μm. Consequently, the cycle characteristics of all-solid-state secondary batteries manufactured using current collector steel foil based on ferritic stainless steel foil decrease.

[0148] On the other hand, if the reduction ratio R in the final cold rolling process is too high, the strain introduced into the intermediate steel through cold rolling will become excessive. In this case, the ends of the intermediate steel may fracture. Therefore, in the final cold rolling process according to this embodiment, the preferred reduction ratio R is 35% to 98%. A more preferred lower limit for the reduction ratio R in the final cold rolling process is 40%, and even more preferably 45%. A more preferred upper limit for the reduction ratio R in the final cold rolling process is 96%, and even more preferably 95%.

[0149] In the final cold rolling process described in this embodiment, other processes besides cold rolling can also be performed. For example, the intermediate steel can be longitudinally cut to process it into any size. In this case, in the final cold rolling process, longitudinal cutting can be performed after cold rolling, after longitudinal cutting, or between cold rolling processes.

[0150] [Heat treatment process]

[0151] In the heat treatment process, the intermediate steel after the final cold rolling process is subjected to heat treatment. In this embodiment, the heat treatment can be performed by passing the steel through a known heat treatment furnace. Furthermore, in this embodiment, the atmosphere for the heat treatment process is preferably an inert gas atmosphere such as nitrogen or a reducing gas atmosphere such as hydrogen.

[0152] The preferred heat treatment temperature in the heat treatment process is 350–700°C. If the heat treatment temperature is too low, the strain cannot be fully released from the intermediate steel. As a result, the half-width at half-maximum (Fw) of the {110} face of the manufactured current collector steel foil may become too high. In this case, heat treatment at a high temperature that allows for the crystallization of the active material can easily cause the current collector steel foil to buckle. On the other hand, if the heat treatment temperature is too high, the strain will be excessively released from the intermediate steel. As a result, the half-width at half-maximum (Fw) of the {110} face of the manufactured current collector steel foil may become too low. In this case, heat treatment at a high temperature that allows for the crystallization of the active material can easily cause the current collector steel foil to bend.

[0153] Therefore, in this embodiment, the heat treatment temperature in the heat treatment process is preferably 350 to 700°C. A more preferred lower limit for the heat treatment temperature is 400°C. A more preferred upper limit for the heat treatment temperature is 650°C. A further preferred heat treatment temperature is 350 to 550°C. In this case, the half-width at half-maximum (Fw) of the {110} plane in the ferritic stainless steel foil of the current collector is stable at 0.45 to 0.52°, and bending of the current collector foil is more easily suppressed by heat treatment at a high temperature that allows for the crystallization of the active material.

[0154] The preferred heat treatment time in the heat treatment process is 1 to 400 seconds. If the heat treatment time is too short, the strain cannot be fully released from the intermediate steel. As a result, the half-width at half-maximum (Fw) of the {110} face in the manufactured current collector steel foil may become too high. In this case, the current collector steel foil is prone to buckling when heat-treated at a high temperature that allows the active material to crystallize. On the other hand, if the heat treatment time is too long, the strain may be excessively released from the intermediate steel. As a result, the half-width at half-maximum (Fw) of the {110} face in the manufactured current collector steel foil may become too low. In this case, the current collector steel foil is prone to bending when heat-treated at a high temperature that allows the active material to crystallize.

[0155] Therefore, in this embodiment, the heat treatment time in the heat treatment process is preferably 1 to 400 seconds. A more preferred lower limit for the heat treatment time is 2 seconds, and even more preferably 3 seconds. A more preferred upper limit for the heat treatment time is 300 seconds, and even more preferably 250 seconds. Furthermore, in this specification, the heat treatment temperature in the heat treatment process refers to the temperature (°C) of the heat treatment furnace used to perform the heat treatment. Additionally, in this specification, the heat treatment time in the heat treatment process refers to the time (seconds) required for the intermediate steel to pass through the heat treatment furnace used to perform the annealing treatment.

[0156] Through the above-described manufacturing process, the current collector steel foil of this embodiment, having the above-described structure, can be manufactured. Furthermore, the above-described manufacturing process is only one example of the manufacturing method for the current collector steel foil according to this embodiment, and the manufacturing method for the current collector steel foil according to this embodiment is not limited to the above-described manufacturing method. Additionally, the manufacturing method for the current collector steel foil according to this embodiment may also implement any of the processes described below. The processes described below are arbitrary and may not be implemented.

[0157] [Tension Annealing Process]

[0158] The method for manufacturing current collector steel foil according to this embodiment may further include a tension annealing process after the final cold rolling process and before the heat treatment process. Tension annealing refers to annealing while applying tension. The intermediate steel that has undergone tension annealing can maintain its flatness through tension.

[0159] When performing the tension annealing process, the preferred annealing temperature is 350–450°C. If the annealing temperature is too low, the effect of tension annealing may not be fully achieved. On the other hand, if the annealing temperature is too high, the dislocation density introduced into the microstructure of the intermediate steel is too low. As a result, the full width at half maximum (Fw) of the {110} peak in the X-ray diffraction curve using CoKα rays may not be sufficiently increased. Therefore, in this embodiment, when performing the tension annealing process, the annealing temperature is preferably 350–450°C.

[0160] When performing tension annealing, the annealing time is not particularly limited. Annealing time can be, for example, 1 to 10 seconds. Furthermore, in this specification, the "annealing temperature" for tension annealing refers to the temperature (°C) of the heat treatment furnace used to perform the annealing treatment. Also, in this specification, the "annealing time" for tension annealing refers to the time (seconds) required for the intermediate steel to pass through the heat treatment furnace used to perform the annealing treatment. Furthermore, when performing tension annealing, the tension applied to the intermediate steel is not particularly limited.

[0161] [Resin Coating Formation Process]

[0162] The method for manufacturing current collector steel foil according to this embodiment may further include a resin coating formation step after the final cold rolling step and before the heat treatment step. As described above, by forming a resin coating, the insulation, heat resistance, and flatness of the current collector steel foil can be improved.

[0163] When the resin coating forming process is performed, a resin coating is formed on the surface of the intermediate steel that has been cold-rolled in the final cold rolling process. As described above, in this embodiment, the resin coating is not particularly limited, and for example, it can be an inorganic-organic mixed resin coating. The method of forming the resin coating is not particularly limited, and can be a known method. For example, the resin coating can also be formed by coating a composition containing resin coating components and allowing it to dry.

[0164] Alternatively, heat treatment for curing the resin coating can be performed as needed. In this case, it is preferable to cure the resin coating during the aforementioned heat treatment process. When the resin coating is cured by heat treatment in the heat treatment process, the strain of the ferritic stainless steel foil can be appropriately controlled while the resin coating is cured. In this case, productivity can be improved.

[0165] [Manufacturing method of all-solid-state secondary batteries]

[0166] The manufacturing method of the all-solid-state secondary battery is not particularly limited, and known methods can be used. As described above, the all-solid-state secondary battery of this embodiment can be manufactured by laminating a thin film of an active material layer and a solid electrolyte layer on or above the current collector steel foil of this embodiment. Here, the method of laminating the thin film is, for example, a vacuum film deposition method represented by sputtering or electron beam evaporation.

[0167] When using sputtering, the sputtering method is not particularly limited, and any well-known sputtering method can be appropriately selected. For example, it can be DC sputtering, RF sputtering, or ion beam sputtering.

[0168] The following examples will provide a more detailed description of the current collector steel foil according to this embodiment. Furthermore, the examples described below are merely illustrative of how to confirm the effectiveness of the current collector steel foil according to this embodiment, and are not intended to limit the scope of the invention.

[0169] Example

[0170] Prepare intermediate steel samples with the thickness (μm) shown in Table 1 for each test number. Furthermore, the intermediate steel samples for each test number were all made of ferritic stainless steel equivalent to SUS444 as specified in JIS G 4305 (2012). Additionally, the intermediate steel samples were all annealed at 840–950°C for 3–30 seconds.

[0171] [Table 1]

[0172]

[0173] Cold rolling was performed on the intermediate steel samples for each test number using rolling mill rolls. The rolling mill rolls used are listed in Table 1. In Table 1, rolls with an arithmetic mean surface roughness Ra less than 0.03 μm are marked as "A". In Table 1, rolls with an arithmetic mean surface roughness Ra of 0.03 μm or more but less than 0.10 μm (excluding 0.10 μm) are marked as "B". In Table 1, rolls with an arithmetic mean surface roughness Ra of 0.10 μm or more but less than 0.30 μm (excluding 0.30 μm) are marked as "C". In Table 1, rolls with an arithmetic mean surface roughness Ra of 0.30 μm or more but less than 0.60 μm (excluding 0.60 μm) are marked as "D". Furthermore, the reduction rate (%) during cold rolling is as described in Table 1.

[0174] Thus, substrates (ferritic stainless steel foil) with the substrate thickness (μm) described in Table 1 were obtained. Annealing as described in the "Annealing Treatment" column was performed on a portion of the obtained substrates with test numbers. Tension annealing (labeled "TA (Tension Annealing)" in Table 1) was performed on substrates with test numbers 6-8. In this embodiment, as tension annealing, a heat treatment of 4 seconds at 400°C was performed. Additionally, bright annealing (labeled "BA (Bright Annealing)" in Table 1) was performed on substrates with test numbers 16 and 17. Bright annealing refers to annealing performed under conditions where the surface of the ferritic stainless steel foil is not nitrided. In this embodiment, as bright annealing, the nitrogen concentration in the atmosphere was set to 0.1% or less, and a heat treatment of 4 seconds at 950°C was performed.

[0175] The composition for forming a siloxane-based resin coating was coated on one side of each of the obtained test numbers. The substrates coated with the composition on one side were subjected to heat treatment for 20 to 300 seconds at the heat treatment temperatures described in Table 1. Note that "-" in the "Heat Treatment Temperature (°C)" column of Table 1 indicates that no heat treatment was performed. Through the above process, the current collector steel foil according to this embodiment was manufactured.

[0176] [Evaluation Test]

[0177] For each test number, the steel foil used for the current collector was subjected to half-width (Fw) measurement test, surface roughness measurement test, buckling evaluation test, bending evaluation test, and cycle characteristic evaluation test.

[0178] [Half-height width (Fw) measurement test]

[0179] The full width at half maximum (FW) of the current collectors was measured using steel foil for each test number to determine the FW of the {110} plane. Specifically, test pieces were fabricated from the steel foil for each test number, and X-ray diffraction patterns were obtained using grazing incidence X-ray diffraction (GIXD). The surface of the test piece without resin coating was identified and used as the observation surface. In GIXD, the X-ray source was CoKα rays, the tube voltage was 40 kV, and the tube current was 135 mA. The X-ray beam was paralleled using a mirror. The incident angle of the Söhler slit was 5°, and the diffraction angle was 2.5°. Twelve conditions were set within the range of 1–25° to ensure that the measurement depth from the observation surface of the test piece ranged from 0.19–4.60 μm for twelve points.

[0180] At each measurement point, the peak of the {110} plane was determined based on the X-ray curve, and the full width at half maximum (FWHM) was calculated. The arithmetic mean of the 12 obtained FWHMs was defined as the FWHM of the {110} plane. Furthermore, the measurement depth was determined by calculating the X-ray penetration depth t with the linear absorption coefficient set to μ and satisfying μt = 1, and converting it to the depth from the observation surface of the test piece. Additionally, the mass absorption coefficient used was 19.11Cr-1.77Mo-78.38Fe (mass%). Furthermore, the density of the ferritic stainless steel foil was 7.75 g / cm³. 3 The half-width Fw (°) of the {110} plane obtained for the current collector steel foil of each test number is shown in Table 1.

[0181] [Surface Roughness Measurement Test]

[0182] Surface roughness tests were performed on the current collector steel foil for each test number to determine the arithmetic mean roughness Ra1 and Ra2. Specifically, test pieces were made from the current collector steel foil for each test number and fixed to a glass substrate. The surface of the test piece with the resin coating was defined as the glass substrate. Three arbitrary positions were determined from the test piece fixed to the glass substrate and used as measurement sites. In this embodiment, the arbitrary direction (direction 1) is parallel to the rolling direction of the ferritic stainless steel foil. The direction perpendicular to direction 1 (direction 2) is parallel to the width direction of the ferritic stainless steel foil.

[0183] At each measurement location, the arithmetic mean roughness (μm) in direction 1 and direction 2 was measured according to the method specified in JIS B 0601 (2001). The roughness meter used for measuring the arithmetic mean roughness was the Surftest SJ-301 (trade name) surface roughness measuring machine manufactured by Mitutoyo Co., Ltd., which is a contact roughness meter. Furthermore, the conditions for calculating the roughness curve are as follows.

[0184] Measuring force: 0.75mN

[0185] Stylus tip shape (when using a contact roughness meter): 2μm R60°

[0186] Cutoff value λc: 0.25mm

[0187] Cutoff value λs: 2.5μm

[0188] Number of intervals: 5

[0189] Measurement speed: 0.25 mm / s

[0190] Reference length: 0.25mm

[0191] Evaluation length: 1.25mm

[0192] The arithmetic mean roughness Ra1 (μm) for direction 1 and the arithmetic mean roughness Ra2 (μm) for direction 2 are shown in Table 1.

[0193] [Compression Evaluation Test]

[0194] A buckling evaluation test was conducted on the current collector steel foil for each test number to evaluate whether buckling occurred. Specifically, an active material layer was formed on the surface of the current collector steel foil for each test number that did not have a siloxane-based resin coating by vapor deposition. In this embodiment, lithium cobalt oxide (LiCoO2) was used as the active material. Furthermore, the dimensions of the current collector steel foil for each test number were 300–600 mm in the width direction. Tension was applied to the current collector steel foil coated with the active material using a 70 mm diameter conveyor roller, while simultaneously undergoing a heat treatment at 700°C for 20 minutes. The applied tension was 5–50 N / mm in the rolling direction of the steel foil. 2 In addition, the conveying speed during heat treatment is 0.1 to 30.0 m / min.

[0195] Visually inspect the current collector steel foils for each test number after heat treatment to check for buckling. More specifically, for each test number of current collector steel foil, if no striped unevenness extending along the rolling direction of the steel foil is observed, it is judged that buckling is unlikely to occur (marked as "E (Excellent)" in Table 1). On the other hand, for each test number of current collector steel foil, if striped unevenness extending along the rolling direction of the steel foil is formed at intervals of a few mm to tens of mm, it is judged that buckling is likely to occur (marked as "NA (Not Acceptable)" in Table 1).

[0196] [Bending Evaluation Test]

[0197] A bending evaluation test was performed on the current collector steel foil for each test number to evaluate whether bending occurred. In this embodiment, a bending evaluation test was also performed on the current collector steel foil for test numbers that were determined to be difficult to bend in the buckling evaluation test. Specifically, test pieces for bending evaluation were made from the current collector steel foil for each test number. The test pieces were 30 mm in the rolling direction of the steel foil and 150 mm in the width direction. An active material layer was formed on the surface of the test pieces by vapor deposition. In this embodiment, lithium cobalt oxide (LiCoO2) was used as the active material. The test pieces with the active material layer formed were heat-treated at 700°C for 20 minutes. One end of the heat-treated test piece in the length direction was fixed to the upper end of a right-angle platform, and the test piece was positioned in contact with the right-angle platform.

[0198] The distance between the lower end of the test piece along its length and the right-angle platform was measured with a ruler and defined as the "warpage" of the test piece. For the current collector foil of each test number, when the warpage was less than 5 mm, it was judged as difficult to bend (marked as "G (Good)" in Table 1). Furthermore, for the current collector foil of each test number, when the warpage was less than 3 mm, it was judged as very difficult to bend (marked as "E (Excellent)" in Table 1). On the other hand, for the current collector foil of each test number, when the warpage was greater than 5 mm, it was judged as easy to bend (marked as "NA (Not Acceptable)" in Table 1).

[0199] [Cyclic Performance Evaluation Test]

[0200] Cyclic characteristic evaluation tests were conducted on the current collector steel foils for each test number to evaluate their cycling characteristics. Furthermore, in this embodiment, cycle characteristic evaluation tests were conducted on the current collector steel foils for test numbers that were determined to be difficult to bend in both the buckling and bending evaluation tests. Specifically, simulated all-solid-state secondary batteries for cycle characteristic evaluation were fabricated from the current collector steel foils for each test number.

[0201] The simulated product was manufactured using the following method. First, a steel foil was cut out and used as a test piece. A positive electrode conductor layer was formed on the surface of the test piece using a DC sputtering apparatus. At this time, Pt was used as the target material, and sputtering was performed without heating in an Ar atmosphere to achieve a film thickness of 1.0 μm. Then, an active material layer was formed on the positive electrode conductor layer on the test piece using an RF sputtering apparatus. The active material in the active material layer was lithium cobalt oxide (LiCoO2), and the film thickness of the active material layer was 0.45 μm. Finally, the test piece with the active material layer formed was subjected to an annealing treatment at 600°C.

[0202] Sputtering was performed using an RF sputtering apparatus to form a solid electrolyte layer on the positive electrode active material layer of an annealed test piece. The electrolyte in the solid electrolyte layer was lithium oxide phosphate (Li3PON4), and the film thickness of the solid electrolyte layer was 1.4 μm. Sputtering was performed using a DC sputtering apparatus to form a negative electrode current collector layer on the solid electrolyte layer formed on the test piece. The conductive material of the negative electrode current collector layer was copper (Cu), and the film thickness of the negative electrode current collector layer was 1.0 μm. Sputtering was performed using an RF sputtering apparatus to form a protective layer on the negative electrode current collector layer formed on the test piece. The protective layer was mainly composed of silicon dioxide (SiO2), and the film thickness of the protective layer was 0.05–1.0 μm. The cycle characteristics of each test number were evaluated using a simulated product prepared as described above.

[0203] Specifically, the simulated products for each test number were subjected to a constant current charge of 0.1C at a rate of C until they reached 4.2V from their resting potential. Then, a constant voltage charge of 4.2V was performed for 20 hours. The simulated products charged using the above method were then subjected to a constant current discharge of 0.1C at a rate of C until they reached 3.0V. Furthermore, in this embodiment, the discharge capacity of this constant current discharge is defined as the initial discharge capacity Qd1 (mAh).

[0204] In this embodiment, a cycle consists of a 0.1C constant current charge until 4.2V is reached, a 20-hour constant voltage charge at 4.2V, and a 0.1C constant current discharge until 3.0V is reached. Nine more charge-discharge cycles are performed on the simulated product whose initial discharge capacity Qd1 (mAh) was measured. In this embodiment, when the initial discharge capacity Qd1 (mAh) is set as the first cycle, the discharge capacity of the constant current discharge in the tenth cycle is defined as the discharge capacity Qd10 (mAh) of the tenth cycle. Furthermore, in this embodiment, the capacity retention rate is defined by the following formula (1).

[0205] Capacity retention rate (%) = 100 × Qd10 / Qd1 (1)

[0206] Furthermore, in this embodiment, the capacity retention rate (%) of each test number is evaluated using relative values. Specifically, the capacity retention rate (%) of test number 14 is used as a benchmark value to evaluate the relative capacity retention rate (%) of each test number. For the current collector steel foil of each test number, when the capacity retention rate is greater than the benchmark value, it is judged to have excellent cycling characteristics (marked as "E (Excellent)" in Table 1). On the other hand, for the current collector steel foil of each test number, when the capacity retention rate is approximately the same as the benchmark value, it is judged to have poor cycling characteristics (marked as "NA1 (Not Acceptable 1)" in Table 1). In addition, for the current collector steel foil of each test number, when the capacity retention rate is less than the benchmark value, it is also judged to have poor cycling characteristics (marked as "NA2 (Not Acceptable 2)" in Table 1).

[0207] [Evaluation Results]

[0208] For the current collector steel foils in tests 1-14, the half-width (Fw) of the {110} face of the ferritic stainless steel foils met the requirements of 0.40-0.52°. As a result, in the buckling evaluation test, buckling was deemed difficult to occur. Furthermore, in the bending evaluation test, the warpage was less than 5 mm, indicating that bending was difficult to occur. In other words, these current collector steel foils, after forming the active material layer, are difficult to buckle or bend when heat-treated at high temperatures to achieve the desired degree of crystallization of the active material.

[0209] Furthermore, the arithmetic mean roughness Ra1 in the rolling direction (direction 1) and the arithmetic mean roughness Ra2 in the width direction (direction 2) of the current collector steel foils in tests 1–9 further met the requirements of 0.03–0.30 μm. As a result, in the cycle performance evaluation test, the capacity retention rate was greater than the benchmark value, indicating excellent cycle performance. That is, after forming the active material layer, these current collector steel foils are difficult to bend or flex during heat treatment at high temperatures that allow the active material to crystallize, and they exhibit excellent cycle performance as all-solid-state secondary batteries.

[0210] Furthermore, the half-width Fw of the {110} face of the ferritic stainless steel foil used for current collectors in tests 1–8, 11, 13, and 14 further satisfied 0.45–0.52°. As a result, in the bending evaluation test, the warpage was less than 3 mm, indicating that bending was extremely difficult to produce.

[0211] On the other hand, the heat treatment temperature of the current collector steel foil in test number 15 was too high. As a result, the half-width at half-maximum (Fw) of the {110} face of the ferritic stainless steel foil used for the current collector was less than 0.40°. Consequently, in the bending evaluation test, the warpage was greater than 5 mm, indicating that it was prone to bending.

[0212] Prior to the heat treatment process, the current collector steel foil in test number 16 underwent bright annealing. No further heat treatment was performed. As a result, the half-width at half-maximum (Fw) of the {110} face of the ferritic stainless steel foil for this current collector was less than 0.40°. Consequently, in the bending evaluation test, the warpage was greater than 5 mm, indicating a tendency to bend.

[0213] Prior to the heat treatment process, the current collector steel foil of test number 17 underwent bright annealing. As a result, the half-width at half-maximum (Fw) of the {110} face of the ferritic stainless steel foil for this current collector was less than 0.40°. Consequently, in the bending evaluation test, the warpage was greater than 5 mm, indicating that it was prone to bending.

[0214] No heat treatment process was performed on the current collector steel foils in tests 18 and 19. As a result, the half-width at half-maximum (Fw) of the {110} face of these current collector steel foils was greater than 0.52°. Consequently, in the buckling evaluation test, they were judged to be prone to buckling.

[0215] The heat treatment temperature of the current collector steel foil in test number 20 was too low. As a result, the half-width at half-maximum (Fw) of the {110} face of the ferritic stainless steel foil for this current collector was greater than 0.52°. Consequently, in the buckling evaluation test, it was determined that buckling was likely to occur.

[0216] The reduction rate in the final cold rolling process of the current collector steel foil in test number 21 was too low. As a result, the half-width at half-maximum (Fw) of the {110} face of the ferritic stainless steel foil for this current collector was greater than 0.52°. Consequently, in the buckling evaluation test, it was determined that buckling was likely to occur.

[0217] The embodiments of this disclosure have been described above. However, the above embodiments are merely examples for implementing this disclosure. Therefore, this disclosure is not limited to the above embodiments, and appropriate modifications can be made to the above embodiments without departing from its spirit.

Claims

1. A steel foil for a current collector, comprising a ferritic stainless steel foil, The ferritic stainless steel foil has a half-value width Fw of a peak of a {110} plane in an X-ray diffraction curve using CoKα rays of 0.40 to 0.52°.

2. The steel foil for current collector according to claim 1, wherein On the surface of the ferritic stainless steel foil, When the arithmetic mean roughness in any direction is defined as Ra1, When the arithmetic mean roughness in a direction perpendicular to the arbitrary direction is defined as Ra2, The Ra1 and the Ra2 are both 0.03 to 0.30 μm.

3. The steel foil for current collector according to claim 1, wherein The ferritic stainless steel foil has a thickness of 5 to 60 μm.

4. The steel foil for current collector according to claim 2, wherein: The ferritic stainless steel foil has a thickness of 5 to 60 μm.

5. The steel foil for current collector according to claim 1, wherein A resin film is formed on the surface of the ferritic stainless steel foil.

6. The steel foil for current collector according to claim 2, wherein: A resin film is formed on the surface of the ferritic stainless steel foil.

7. The steel foil for current collector according to claim 3, wherein A resin film is formed on the surface of the ferritic stainless steel foil.

8. The steel foil for current collector according to claim 4, wherein A resin film is formed on the surface of the ferritic stainless steel foil.

9. An all-solid-state secondary battery, comprising: The steel foil for current collector according to any one of claims 1 to 8; active material layer; a solid electrolyte layer; and Current collector layer.

Citation Information

Patent Citations

  • Lithium battery

    JP2003178753A

  • Lithium ion battery negative electrode and lithium ion battery

    JP2016186881A

Cited By

  • battery

    EP4787495A1